2013
DOI: 10.1016/s1995-7645(13)60061-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and antioxidation of Nrf2/ARE pathway in traumatic brain injury

Abstract: After TBI the Nrf2/ARE pathway is activated and the activity of Nrf2 transcription regulation increases. However, the regulation dose not occur in the gene transcription level and only could increase the Nrf2 protein level, while the mRNA expression level has no obvious change. The nerve cell protective effect of Nrf2/ARE pathway in TBI achieves through inhibiting the oxidative stress injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
0
23
2
Order By: Relevance
“…These antioxidant and detoxifying factors encompass many important protective mechanisms for secondary brain injury following traumatic brain injury (Miller et al, 2014;Sandberg et al, 2014). Previous studies have found that expression of Nrf2 begins to increase 2 h after traumatic brain injury, and its expression peaks after 24 h. Nrf2 expression then gradually decreases and returns to normal levels 3 to 5 days later (Cheng et al, 2013). The degree of traumatic brain injury in Nrf2 knockout mice is significantly more severe compared to wild type mice, and administration of drugs that up-regulate Nrf2 protein expression significantly reduces apoptosis of neurons and improves neurological function after traumatic brain injury Xie et al, 2014;Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These antioxidant and detoxifying factors encompass many important protective mechanisms for secondary brain injury following traumatic brain injury (Miller et al, 2014;Sandberg et al, 2014). Previous studies have found that expression of Nrf2 begins to increase 2 h after traumatic brain injury, and its expression peaks after 24 h. Nrf2 expression then gradually decreases and returns to normal levels 3 to 5 days later (Cheng et al, 2013). The degree of traumatic brain injury in Nrf2 knockout mice is significantly more severe compared to wild type mice, and administration of drugs that up-regulate Nrf2 protein expression significantly reduces apoptosis of neurons and improves neurological function after traumatic brain injury Xie et al, 2014;Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When oxidative stress stimulus occurs, it is decoupled with Keapl through phosphorylation, transfers into nucleus, combines with antioxidant response element (ARE) sequence, forms Nrf2/ARE pathway and then starts the gene expression of phase II detoxifying enzymes and antioxidases (H0-1, NQO1, etc) regulated by ARE. Nrf2/ARE pathway plays an important role in endogenous anti-oxidation process in vivo and can be induced by external factors (14).…”
Section: Neuroprotection and Emerging Roles Of Nrf2mentioning
confidence: 99%
“…These evidences demonstrate that activation of the Nrf2-ARE pathway is beneficial for TBI. (16) It is now accepted that the Nrf2-ARE pathway can be regulated in many different ways (14,16,36).…”
Section: Neuroprotection and Emerging Roles Of Nrf2mentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear factor (erythroid-derived 2)-like 2 (NFE2L2 or Nrf2) signaling pathway regulates the level of expression of antioxidant proteins that protect against oxidative injury induced by trauma and inflammation, and this pathway has increasingly attracted attention in studies of the molecular mechanism of ROS in TBI (57). In rat and mouse experiments, activation of the Nrf2 pathway has been found to inhibit ROS-induced damage in brain tissue (58).…”
Section: Clinical Treatmentmentioning
confidence: 99%